The Influence of Institutional Differences on Control Mechanisms in Alliances - Zeng, Wei; Lillis, Anne M.; Grafton, Jennifer; Dekker, Henri C. (The Accounting Review, 2022)
ABSTRACT Cross-border alliances expose firms to heightened risks, posing different governance and control challenges than domestic alliances. We examine the impact of differences in alliance partner countries' institutional environments. Analysis of survey data supports our contention that cross-border alliances involve a greater reliance on formal controls, particularly when firms collaborate with partners in countries with a weaker institutional environment. These relations exist regardless of governance structure (i.e., equity or non-equity alliance) that prior research considers a critical choice for addressing cross-border alliance risks. Additional analyses show that four subdimensions of institutional characteristics (voice and accountability, regulatory quality, rule of law, and control of corruption) and one subdimension of formal controls (behavior controls) are the main drivers in the association between institutional distance and reliance on formal controls. These findings demonstrate the distinct impact of institutional environment as a country-level determinant of alliance control choices. Data Availability: Due to confidentiality agreements with respondents, the data cannot be released publicly. JEL Classifications: D23; D82; L22; M4.